2016
DOI: 10.1155/2016/7925052
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and Impact of Stigma and Discrimination among People on Antiretroviral Therapy in Dar es Salaam: A Qualitative Perspective

Abstract: Background. The impact of stigma on adherence to antiretroviral therapy (ART) has been less studied in Tanzania. Recent studies indicate that people on ART still experience stigma. Qualitative information on the subject matter is especially insufficient. Objective. This paper reports on the dimensions of stigma and discrimination and their impact on adherence to ART as experienced by people living with HIV (PLHIV). Design. A phenomenological approach was used to gather information on the lived experiences of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 25 publications
3
38
1
2
Order By: Relevance
“…This implies that a lack of financial independence, which is compounded by the experience of IPV, hinders women's access to ARV treatment. Similar studies done in Dar-es Salaam (11) and Botswana (12) found that women LWHA fail to attend CTC due to a lack of fare for transport. Thus, they run short of ARVs, which is associated with poor adherence to ARV treatment, which results in treatment failure due to a lack of fare to attend CTC.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…This implies that a lack of financial independence, which is compounded by the experience of IPV, hinders women's access to ARV treatment. Similar studies done in Dar-es Salaam (11) and Botswana (12) found that women LWHA fail to attend CTC due to a lack of fare for transport. Thus, they run short of ARVs, which is associated with poor adherence to ARV treatment, which results in treatment failure due to a lack of fare to attend CTC.…”
Section: Discussionsupporting
confidence: 60%
“…According to the National AIDS Control Program Care and Treatment report, it is estimated that 21–30% of PLHIV in Tanzania have registered at care and treatment clinics (CTCs), and that 63–83% of those eligible for treatment are receiving ARV medication. The availability of ARV treatment has a significant impact on prolonging the lives of HIV-infected people (11, 12). Little is known about the challenges facing women LWHA as victims of IPV in Tanzania.…”
Section: Introductionmentioning
confidence: 99%
“…En la relación específica con la adherencia a TARV en mujeres, un primer elemento que impacta y que ha sido mencionado en otras investigaciones, es el estigma que aún rodea a la infección por VIH 24,32 , el que actúa sobre el imaginario personal de las mujeres en relación al VIH, la discriminación vivida y percibida, y la propia discriminación hacia el imaginario de perfil de personas afectadas por el VIH. Como muestran los resultados, el estigma está asociado no sólo a padecer de esta infección, sino a ser una mujer que vive con ella, lo que es motivo de doble discriminación.…”
Section: Artículo Originalunclassified
“…23 . Otros estudios han mostrado que la adherencia a la TARV en mujeres estaría relacionada con temor a la discriminación 24 , a la divulgación de su diagnóstico…”
unclassified
“…The persistence of HIV associated stigma, is a threat to progress in the control of HIV internationally (Stangl & Grossman, 2013), a barrier to testing (Dapaah & Senah, 2016), prevention of mother-to-child transmission (Turan & Nyblade, 2013), and, once diagnosis is confirmed, stigma remains a barrier to PLWH accessing adequate healthcare (Bogart et al, 2013;Dasgupta, Sullivan, Dasgupta, Saha, & Salazar, 2013). It is also associated with non-adherence to antiretroviral therapy (ART), increasing the risk of viral resistance (Mhode & Nyamhanga, 2016;Sweeney & Vanable, 2016).…”
Section: Introductionmentioning
confidence: 99%